Glomerulonephritis Associated with Antibody to Glomerular Basement Membrane. Issue 5935 (5th October 1974) - Sissons, J. G. P.; Evans, D. J.; Peters, D. K.; Eisinger, A. J.; Boulton-Jones, J. M.; Simpson, I. J.; Macanovic, M.
Abstract : Glomerulonephritis associated with antibody to glomerular basement membrane, shown by linear staining of the glomerular basement membrane with fluoresceinated anti-IgG antisera, was found in only 10 out of 400 (2·5%) renal biopsy specimens studied by immunofluorescence. Seven of these cases had rapidly progressive glomerulonephritis, five with lung haemorrhage (Goodpasture's syndrome) and two without, and three had less severe nephritis without lung haemorrhage. Circulating antibody to glomerular basement membrane, measured by a passive haemagglutination technique and by indirect immunofluorescence, was detected in the serum of all patients with rapidly progressive glomerulonephritis by both techniques but only by the passive haemagglutination method in two of the other three patients. Two patients died of their lung haemorrhage, one despite bilateral nephrectomy, and lung haemorrhage and circulating antibody to glomerular basement membrane persisted after bilateral nephrectomy in another patient.